Teaching English modals to speakers of Chabacano in Zamboanga City - Urian, Victoria (Castaneda) 1920- ([Quezon City publisher not identified], 1965)
This paper instructional materials in the teaching of English modals intended for English teachers in Zamboanga City whose students are Chabacano speakers are presented in this study. Based on a contrastive analysis of English and Chabacano modals, problems that were likely to be met in learning English modals were identified.
Thesis (Master of Arts in Teaching)--University of the Philippines.
Keywords: English languages -- Grammar